Acceptance and Use of Mobile Payments in Healthcare Delivery among Private Providers in the Ayawaso Municipality - Azietsi-Bokor, W. (University of Ghana, 2018)
In recent years, mobile phone use in healthcare delivery has been the focus of healthcare research. Of great interest to researchers is to study and understand the acceptance and use of mobile payments in health delivery since mobile payments serves as a complementary service to mobile health. Mobile payments provides a solution to the growing moral hazards and security risks associated with cash payments in healthcare delivery and also lessens the institutionalization of informal payments in health delivery. A census was conducted on all health facilities within the Ayawaso municipality and the results analyzed with the help of structural equation modelling (SEM) via the AMOS software package in SPSS version 22. The constructs were tested and found to have high validity. Fifty-three percent of providers were found to be currently accepting mobile payments at their facilities. The study concluded that performance expectancy and perceived cost are strongly associated with the intention to use mobile payment systems and the actual use of mobile payment systems and recommended that healthcare providers should analyze the task-technology fit of payments and liaise with mobile money operators to shorten the series of steps needed towards completion of mobile payments to save time for patients and providers.
Thesis (MPh)
Keywords: Healthcare; Structural; Delivery; Mobile phone